Distributions and controls of carbonate parameters in offshore oil and gas fields of the Beibu Gulf and adjacent northern South China Sea (nSCS) shelf during the fall season - Hanjun Yin; Wei Yang; Minxia Zhang; Xiaojuan Peng; Hong Tang; Jianjun Ye; Chuqian Lu (Marine Environmental Research, 2026)

Hyp-retro: hypernetwork-guided preference-conditioned retrosynthetic planner - Jingwen Wang; Shuan Liu; Shaoye Zhang; Jianbo Qiao; Guanhe Li; Hanjun Zhao; Xiangxiang Zeng; Jinjin Li; Changhang Lin; Chen Su; Leyi Wei (Molecular Diversity, 2026)

Prevalence, molecular characterization and zoonotic potential of Cryptosporidium spp. in horses from diverse husbandry systems across four provinces of northern and eastern China - Weimeng Qin; Fanggu Zhu; Yuhan Guan; Hanjun Zeng; Zhongkai Zhang; Yiyi Cui; Kuan Zhang; Wei Zhao; Jiangqiong Ke (The Veterinary Journal, 2026)

Nitrogen-doped porous biomass-derived carbons for enhanced hydrophobicity, microwave absorption and thermal insulation - Siyu Chen; Zhiyong Chen; Lu Tang; Jimei Xue; Zhijun Wang; Ying Li; Hanjun Wei (Fuel, 2026)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

Exploring the association between air pollution and urogenital congenital anomalies: a global ecological analysis - Kebin Chen; Hanjun Liu; Tingting Wang; Manjun Luo; Xiaorui Ruan; Mengting Sun; Ziye Li; Jianhui Wei; Jiabi Qin (Environmental Pollution, 2025)

A tentative ice force formula for vertical piles in Bohai Sea based on model tests - Wei Li; Hanjun Yin; Jianqiao Sun; Yang Gao; Mengzhu Zhang (Ocean Engineering, 2025)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

PKHD1L1, a gene involved in the stereocilia coat, causes autosomal recessive nonsyndromic hearing loss - Shelby E. Redfield; Pedro De-la-Torre; Mina Zamani; Hanjun Wang; Hina Khan; Tyler Morris; Gholamreza Shariati; Majid Karimi; Margaret A. Kenna; Go Hun Seo; Hongen Xu; Wei Lu; et al. (Human Genetics, 2024)
Identification of genes associated with nonsyndromic hearing loss is a crucial endeavor given the substantial number of individuals who remain without a diagnosis after even the most advanced genetic testing. PKHD1L1 was established as necessary for the formation of the cochlear hair-cell stereociliary coat and causes hearing loss in mice and zebrafish when mutated. We sought to determine if biallelic variants in PKHD1L1 also cause hearing loss in humans. Exome sequencing was performed on DNA of four families segregating autosomal recessive nonsyndromic sensorineural hearing loss. Compound heterozygous p.[(Gly129Ser)];p.[(Gly1314Val)] and p.[(Gly605Arg)];p[(Leu2818TyrfsTer5)], homozygous missense p.(His2479Gln) and nonsense p.(Arg3381Ter) variants were identified in PKHD1L1 that were predicted to be damaging using in silico pathogenicity prediction methods. In vitro functional analysis of two missense variants was performed using purified recombinant PKHD1L1 protein fragments. We then evaluated protein thermodynamic stability with and without the missense variants found in one of the families and performed a minigene splicing assay for another variant. In silico molecular modeling using AlphaFold2 and protein sequence alignment analysis were carried out to further explore potential variant effects on structure. In vitro functional assessment indicated that both engineered PKHD1L1 p.(Gly129Ser) and p.(Gly1314Val) mutant constructs significantly reduced the folding and structural stabilities of the expressed protein fragments, providing further evidence to support pathogenicity of these variants. Minigene assay of the c.1813G>A p.(Gly605Arg) variant, located at the boundary of exon 17, revealed exon skipping leading to an in-frame deletion of 48 amino acids. In silico molecular modeling exposed key structural features that might suggest PKHD1L1 protein destabilization. Multiple lines of evidence collectively associate PKHD1L1 with nonsyndromic mild–moderate to severe sensorineural hearing loss. PKHD1L1 testing in individuals with mild–moderate hearing loss may identify further affected families.

Study on engineering application method of large-scale reaction mechanism in knock prediction - Hanjun Xu; Jian Wu; Jingsi Wei; Ceyuan Chen; Mingjia Liu; Shan Wu (Fuel, 2023)

The expansion of mesophyll cells is coordinated with the division of chloroplasts in diploid and tetraploid Arabidopsis thaliana - Hanjun He; Wei Xie; Zhixin Liang; Hong Wu; Mei Bai (Planta, 2021)